Sociology of media - "Sinha, Sushil Kumar" (Delhi, 2004)
This book is about the impact of Doodarshan on tribals in different sphere. It has tries to analyse the relationship between tribal community and Doordarshan and their exposure to this important and effective media of mass communication towards their educational, cultural, economic, political as well as social development. It has also tried to analyse the impact of doordarshan on tribals towards continuity and change.
Keywords: Mass Media